Spontaneous Browning of White Adipose Tissue Improves Angiogenesis and Reduces Macrophage Infiltration After Fat Grafting in Mice - Lin, Jiayan; Zhu, Shaowei; Liao, Yunjun; Liang, Zhuokai; Quan, Yuping; He, Yufei; Cai, Junrong; Lu, Feng (Frontiers in Cell and Developmental Biology, 2022)
Abstract Background: Fat grafting is a frequently used technique; however, its survival/ regeneration mechanism is not fully understood. The browning of white adipocytes, a process initiated in response to external stimuli, is the conversion of white to beige adipocytes. The physiologic significance of the browning of adipocytes following transplantation is unclear. Methods: C57BL/6 mice received 150 mg grafts of inguinal adipose tissue, and then the transplanted fat was harvested and analyzed at different time points to assess the browning process. To verify the role of browning of adipocytes in fat grafting, the recipient mice were allocated to three groups, which were administered CL316243 or SR59230A to stimulate or suppress browning, respectively, or a control group after transplantation. Results: Browning of the grafts was present in the center of each as early as 7 days post-transplantation. The number of beige cells peaked at day 14 and then decreased gradually until they were almost absent at day 90. The activation of browning resulted in superior angiogenesis, higher expression of the pro-angiogenic molecules vascular endothelial growth factor A (VEGF-A) and fibroblast growth factor 21 (FGF21), fewer infiltrating macrophages, and ultimately better graft survival (Upregulation, 59.17% ± 6.64% vs. Control, 40.33% ± 4.03%, *p < 0.05), whereas the inhibition of browning led to poor angiogenesis, lower expression of VEGF-A, greater macrophage infiltration, and poor transplant retention at week 10 (Downregulation, 20.67% ± 3.69% vs. Control, 40.33% ± 4.03%, *p < 0.05). Conclusion: The browning of WAT following transplantation improves the survival of fat grafts by the promotion of angiogenesis and reducing macrophage infiltration.